Clinical spectrum and prognostic value of CNS MOG autoimmunity in adults: The MOGADOR study. (22nd May 2018) - Cobo-Calvo, Alvaro; Ruiz, Anne; Maillart, Elisabeth; Audoin, Bertrand; Zephir, Helene; Bourre, Bertrand; Ciron, Jonathan; Collongues, Nicolas; Brassat, David; Cotton, Francois; Papeix, Caroline; Durand-Dubief, Francoise; et al.
Abstract : Objective: To describe clinical and radiologic features associated with myelin oligodendrocyte glycoprotein antibodies (MOG-Ab) in a large French nationwide adult cohort, to assess baseline prognostic features of MOG-Ab-associated diseases after a first acute demyelinating syndrome, and to evaluate the clinical value of MOG-Ab longitudinal analysis. Methods: Clinical data were obtained from 197 MOG-Ab-positive patients ≥18 years of age. Complete imaging data were available in 108, and 54 serum samples were eligible for longitudinal evaluation. For survival analysis comparison, 169 aquaporin-4 antibody (AQP4-Ab)-positive patients from the NOMADMUS database were included. Results: Median age at onset was 36.46 (range 18.0–76.8) years, and patients were predominantly white (92.9%) with male:female ratio, 1.1. Clinical phenotype at onset included optic neuritis or myelitis in 90.86%, isolated brainstem or encephalopathy syndromes in 6.6%, and a combination of syndromes in 2.5%. Distinctive brain MRI findings in MOG-Ab-positive patients were thalamic and pontine lesions. Cortical and leptomeningeal lesions were found in 16.3% and 6.1%, respectively. The probability of reaching a first relapse after 2 and 5 years was 44.8% and 61.8%, respectively. MOG-Ab-positive patients were at lower risk at presentation of further clinical relapse (hazard ratio [HR] 0.45, 95% confidence interval [CI] 0.26–0.79) compared to AQP4-Ab-positive individuals. MOG-Ab-positive individuals had a lower risk of reaching Disability Status Scale score of 3.0 (HR 0.46, 95% CI 0.22–0.94) and visual acuity of 20/100 (HR 0.23, 95% CI 0.07–0.72). Finally, MOG-Ab titers were higher at relapse than in remission ( p = 0.009). Conclusion: In adults, MOG-Ab-associated disease extends beyond clinical and radiologic abnormalities in the optic nerve and spinal cord. Despite the relapsing course, the overall visual and motor outcome is better compared with AQP4-Ab-positive patients.